ANALISIS KESESUAIAN INSTRUMEN PENGKAJIAN KESEHATAN MULUT ORAL HEALTH ASSESMENT TOOL (OHAT) DAN ORAL ASSESMENT SCALE (OAS) PADA PASIEN CRITICAL CARE - Ayu, Yanu; Karunia Estri, Arimbi; Dede Yoshima Nekada, Cornelia (Journal Healthcare Education, 2025)
Oral hygiene is very important to prevent infection in patients in the ICU, especially those using ventilators. The mouth's natural cleansing mechanism can be disrupted, increasing the risk of ventilator-associated pneumonia (VAP) due to microorganisms that develop in the oropharynx and spread to the airways within 48 hours. "This study aims to compare the Oral Health Assessment Instrument (OHAT) and Oral Assessment Scale (OAS) scores in assessing the oral health condition of ICU & HCU patients at Atama Jaya Hospital, North Jakarta." With a quantitative research design and comparative analytical observational approach, the sample consisted of 27 patients selected according to the inclusion criteria. Data were collected using OHAT and OAS, and analyzed using the Mann Whitney statistical test. The results showed that there was a significant difference between OHAT and OAS in assessing patients' oral health (p=0.000). The OAS demonstrated a higher median score, reflecting higher sensitivity in detecting variations in oral health and providing a more inclusive assessment than the OHAT. Conclusion: OAS is better at identifying significant oral health problems.